Growth, Nitrogen Fixation, and Spectral Attenuation in Cultivated Trichodesmium Species - Prufert-Bebout, Lee (1993)
Physiological studies of Trichodesmium species have been hindered by difficulties in maintaining actively growing, nitrogen-fixing cultures. Previous cultivation successes have not been widely duplicated. We present here a simple modified seawater medium and handling techniques which have been used to maintain actively growing Trichodesmium thiebautii in laboratory culture for over 1 year. The cultured population, isolated from coastal Atlantic waters, has a growth rate of 0.23 division day(-1) and exhibits light-dependent nitrogen fixation during exponential growth. Various morphologies, including solitary trichomes, and aggregates (spherical puffs and fusiform tufts) are present during growth. Spectral and scalar irradiance were measured within naturally occurring (coastal Atlantic) aggregates with small (diameter, 50 to 70 μm) spherical fiber-optic sensors. In contrast to naturally occurring puffs, cultivated Trichodesmium aggregates exhibited spectral properties consistent with low-light adaptation. Cultivated puff-type aggregates were also examined by using oxygen microelectrodes. The simple medium and approach used for cultivation should be easily reproducible and amenable to further manipulations and modifications useful for physiological studies of Trichodesmium spp. in culture.